2017
DOI: 10.1038/s41598-017-01054-2
|View full text |Cite
|
Sign up to set email alerts
|

Common sequence variants affect molecular function more than rare variants?

Abstract: Any two unrelated individuals differ by about 10,000 single amino acid variants (SAVs). Do these impact molecular function? Experimental answers cannot answer comprehensively, while state-of-the-art prediction methods can. We predicted the functional impacts of SAVs within human and for variants between human and other species. Several surprising results stood out. Firstly, four methods (CADD, PolyPhen-2, SIFT, and SNAP2) agreed within 10 percentage points on the percentage of rare SAVs predicted with effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
(37 reference statements)
3
31
2
Order By: Relevance
“…Additionally, we find that the properties of rare variants remain close to those of common variants. These findings contrast with other observations [9], which suggest that common variants have more impact on molecular function than rare variants. In this study, only for a few proteomics properties, such as the thermal stability and abundance of the affected proteins, common variants appear closer in character to disease-associated variants than to rare variants.…”
Section: Rare Variants Are Similar To Common Variantscontrasting
confidence: 99%
See 2 more Smart Citations
“…Additionally, we find that the properties of rare variants remain close to those of common variants. These findings contrast with other observations [9], which suggest that common variants have more impact on molecular function than rare variants. In this study, only for a few proteomics properties, such as the thermal stability and abundance of the affected proteins, common variants appear closer in character to disease-associated variants than to rare variants.…”
Section: Rare Variants Are Similar To Common Variantscontrasting
confidence: 99%
“…Thus our results indicate two competing trends for disease-associated variants: (i) disease-associated variants tend to localise to more abundant and stable proteins, which may suggest that these proteins are more sensitive to perturbation by variants; (ii) disease-associated variants in protein cores tend to localise to less stable proteins, which is consistent with the idea that such proteins might be more easily destabilised to a degree at which function is deleteriously impacted (see Discussion). gnomAD common data also show negative correlations with protein stability, for variants occurring at the core; this could potentially support the argument presented by Mahlich and colleagues [9] that common variants could affect molecular function more than rare variants. However, we believe this is more likely to be due to the fact that very few common variants localise to protein cores, as shown by Figure 5B, resulting in sparse statistics (i.e.…”
Section: Proteomics and Transcriptomics Features Associate With Variasupporting
confidence: 78%
See 1 more Smart Citation
“…Previous efforts to compare and contrast predictors of general variant impact have found that methods are correlated in their predictions, largely due to similar design objectives, overlapping training sets, and/or feature sets (Ioannidis et al, ; Mahlich et al, ). Interestingly, for predictors of mutation‐induced stability change, correlations were found to be small in previous evaluations (Khan & Vihinen, ; Potapov et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Single amino acid variants (SAVs) have been found to be relevant for the molecular function of proteins [1]. The impact of different SAVs has been predicted in silico showing that, within human, more common SAVs (observed in more than 5% of the population) tend to have a larger impact on protein function than the rare ones (observed in less than 1% of the population [1]. The effect of common SAVs (gain or loss of functionality) on the survival of the species remains, at least partially, unknown.…”
Section: Introductionmentioning
confidence: 99%